Fostering students’ problem-solving skills through biology learning model integrated with Kurikulum Merdeka - Baiq Fatmawati; M. Marzuki; Fenny Roshayanti; Purwati Kuswarini Suprapto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Kurikulum Merdeka is a learning experience framework that offers flexibility and focuses on essential content, character development, and students' competencies. Teachers had the discretion to develop their modules to choose, design, and organize the learning contents for students, based on their needs. By using that module, there is more flexibility and independence either for teachers and students, while enhancing the relevance, interactivity, and effectiveness of learning. This research aims to develop problem-based teaching modules on biology based on Kurikulum Merdeka as a reference in the learning process. This research and development, referring to Borg and Gall's model, consists of (1) research and information collection, (2) planning, (3) developing a preliminary form of the product, (4) preliminary field testing, and (5) main product revision. The participants in this development research are teachers as learning experts and students of a senior high school in one of the districts of East Lombok as a subject in limited trials. Data collection used closed questionnaires to determine the feasibility and ideality of the instrument. Data analysis using quantitative descriptive analysis involves analyzing the results of instrument feasibility and ideality from experts and students. The results show that the developed module was included in the very feasible and ideal learning resources. The readability test of the worksheet after limited trials was included in the good category for the biodiversity content, and quite good for the virus and ecosystem content. Therefore, the problem-based teaching module on biology content in phase E of grade XI of senior high school is considered feasible.